â€œTEORI DIRIâ€ SEBUAH TAFSIR MAKNA SIMBOLIK (PENDEKATAN TEORI DRAMATURGI ERVING GOFFMAN) - Mustaâ€™in, Mustaâ€™in (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
When humans interact each other, he wanted to manage the impression that he hopes will grow on otherpeople to it. Goffman's dramaturgy approach views that every person doing the show for others. Dramaturgy theoryapproach also attempts to connect action with its meaning, and behavior with the determinant. In view of the dramaturgyof social life, the meaning is not the cultural heritage, socialization, or institutional arrangement, the embodiment ofpsychological and biological potency, but the achievement of problematic human interactions. The meaning of a symbol,appearance or behavior is entirely versatile as possible, while, and are situational. Focus of dramaturgy approach is not whatpeople are doing, what they want to do, or why they do, but how they do it.